Student’s Entrepreneurship Interest in Terms of Contextual and Personal Factor - Tegowati Tegowati; Dian Palupi; Widhi Ariestianti Rochdianingrum (Indonesian Journal of Business and Entrepreneurship (IJBE), 2019)
This study aims to review the interests of student entrepreneurship from contextual factors and personal factors. The population in this study was students in East Java with a total sample of 125. The sampling technique used was accidental sampling and data analysis using SEM. The results of this study are: 1) there is an influence of the contextual factors on the interest in entrepreneurship. This is based on standardized output parameter coefficient of 0.524 with p= *** (significant at p = 0.001). 2) There is an influence of personality factors on the interest in entrepreneurship. This is indicated by the standardized output parameter coefficient of 0.472 which is significant at p = 0.001 (p = ***). The conclusion of this study is contextual factors and personality factors influence the interest in student entrepreneurship.Keywords: interest in entrepreneurship, contextual factors, personality factors, student’s entrepreneurship, improve student competency